2011
DOI: 10.1002/chem.201003417
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antioxidant Activity of Peptide‐Based Ebselen Analogues

Abstract: A series of di- and tripeptide-based ebselen analogues has been synthesized. The compounds were characterized by (1)H, (13)C, and (77)Se NMR spectroscopy and mass spectral techniques. The glutathione peroxidase (GPx)-like antioxidant activity has been studied by using H(2)O(2) , tert-butyl hydroperoxide (tBuOOH), and cumene hydroperoxide (Cum-OOH) as substrates, and glutathione (GSH) as a cosubstrate. Although all the peptide-based compounds have a selenazole ring similar to that of ebselen, the GPx activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 65 publications
1
36
1
Order By: Relevance
“…Attempted the synthesis of the Se‐carboxymethylated derivative 66 was also unsuccessful,48 it clearly indicates that the catalytically active selenol (e.g., 65 ) is not produced during the catalytic cycle. This is a characteristic catalytic feature of ebselen and its analogues 21. This observation is in sharp contrast with our computational results (natural charge calculations) on 52 / 34 a , which predicted that such system should overcome the thiol exchange to produce catalytically active selenol through desired electronic effects.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Attempted the synthesis of the Se‐carboxymethylated derivative 66 was also unsuccessful,48 it clearly indicates that the catalytically active selenol (e.g., 65 ) is not produced during the catalytic cycle. This is a characteristic catalytic feature of ebselen and its analogues 21. This observation is in sharp contrast with our computational results (natural charge calculations) on 52 / 34 a , which predicted that such system should overcome the thiol exchange to produce catalytically active selenol through desired electronic effects.…”
Section: Resultscontrasting
confidence: 99%
“…This attracted our attention towards the synthesis and studies on the GPx‐like activity of the ebselen analogues and diselenides that contain amino acid functions. During the course of our study, Satheeshkumar and Mugesh communicated the synthesis and GPx‐like activity of peptides that contain ebselen analogues and diselenides 21. It has been demonstrated that the presence of a valine residue in the peptide enhanced the antioxidant property by producing the catalytically active selenol intermediate, which is generally not predominant in the catalytic cycle of ebselen.…”
Section: Introductionmentioning
confidence: 97%
“…Kandhan et al . (Satheeshkumar & Mugesh, ) demonstrated that the introduction of valine at N‐terminus significantly enhanced the antioxidant activity. It is consistent with our results.…”
Section: Resultsmentioning
confidence: 97%
“…Direct reduction of benzisoselenazolones with different reducing agents -sodium borohydride, hydrazine, ascorbate or phosphoric acid (h), [33][34][35][36] nucleophilic substitution of o-iodobenzamides with lithium diselenide (i), 37 under radical conditions from the reaction of 2-benzylselenobenzamides with triphenyltin hydride and further treatment with benzoyl peroxide (j) 38 and few protocols starting from 2,2-diselenobis(benzoic acid) -through the formation of the corresponding dichloride and further reaction with amine (k) 39 or by EDC (l) 40 and DCCmediated (m) 41 coupling reactions (Scheme 2).…”
Section: -32mentioning
confidence: 99%